2008
DOI: 10.1126/science.1163766
|View full text |Cite
|
Sign up to set email alerts
|

Selfish Genetic Elements Promote Polyandry in a Fly

Abstract: It is unknown why females mate with multiple males when mating is frequently costly and a single copulation often provides enough sperm to fertilize all a female's eggs. One possibility is that remating increases the fitness of offspring, because fertilization success is biased toward the sperm of high-fitness males. We show that female Drosophila pseudoobscura evolved increased remating rates when exposed to the risk of mating with males carrying a deleterious sex ratio-distorting gene that also reduces sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(133 citation statements)
references
References 24 publications
7
124
2
Order By: Relevance
“…The data on response by males to exposure to a previously mated female has to be interpreted cautiously, because focal males are likely to have remated with this female. Drosophila pseudoobscura females typically remate after 4 days [20], and so are likely to have mated with the focal male at least once. Males of this species can mate with three females a day, each day for several days without any loss of ability to mate [40], so the impact of this may have been minor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on response by males to exposure to a previously mated female has to be interpreted cautiously, because focal males are likely to have remated with this female. Drosophila pseudoobscura females typically remate after 4 days [20], and so are likely to have mated with the focal male at least once. Males of this species can mate with three females a day, each day for several days without any loss of ability to mate [40], so the impact of this may have been minor.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we examined the impact of social environment on a male's ability to acquire matings and on longevity. We compared social environment effects across two Drosophila species: the monandrous D. subobscura, and the closely related polyandrous species Drosophila pseudoobscura [16,19,20]. As males of a monandrous species are only subjected to pre-copulatory sexual selection while males of polyandrous species are subjected to both pre-and post-copulatory sexual selection, we expected that the presence of rivals before copulation would have a more profound impact on the fitness (reproductive success and survival) of males of the monandrous species than the polyandrous one.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore predict that females that are at risk of SR should evolve to remate more frequently and at a higher rate. This possibility was examined using experimental evolution in replicate populations, demonstrating that females do indeed rapidly evolve higher remating rates in the presence of SR (figure 3; [69]). This effect could be attributed to the presence of SR and not due to the associated female-biased population sex ratio, as SR alone did not result in evolution of higher female remating rates.…”
Section: Do Selfish Genetic Elements Promote Polyandry?mentioning
confidence: 99%
“…The proportion of experimental evolution line Drosophila pseudoobscura females remating at their first opportunity, for each selection regime (n ¼ 11 lines), when offered standardized stock males, showing median, interquartile range, and range (*p ¼ 0.0383; n.s., not significant). Adapted from Price et al [69] rstb…”
Section: Do Selfish Genetic Elements Promote Polyandry?mentioning
confidence: 99%
“…It has also been shown that polyandry may halt the spread of selfish genetic elements (Price et al, 2008). Hence, polyandry may not only prevent inbreeding but also have significant implications for the evolution of mating systems.…”
Section: Introductionmentioning
confidence: 99%